Obesiti dan gaya hidup murid perempuan sekolah rendah di negeri Kedah Darul Aman - Faridah Abdul Rahman (Tanjong Malim, 2009)
Obesiti dan gaya hidup murid perempuan sekolah rendah di negeri Kedah Darul Aman by Faridah Abdul Rahman